Retraction notice to "Myoinositol supplementation for the prevention of gestational diabetes in at-risk patients. Systemativ review and meta-analysis" [Curr. Res. Pharmacol. Drug Discov. 4C (2023) 100140] - Anthéa Bertrand; Denis Gallot; Bruno Pereira; Amélie Delabaere (Elsevier, 2023)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/policies/article-withdrawal).<This article has been withdrawn at the request of Author>